Triorganotin Isothiocyanates Affect Migration and Immune Check-point Receptors in Human Triple-negative Breast Carcinoma MDA-MB-231 Cells - Hunakova, Luba; Horvathova, Eva; Gronesova, Paulina; Bobal, Pavel; Otevrel, Jan; Brtko, Julius (Anticancer research, 2019)
BACKGROUND/AIM: Triple-negative breast cancer (TNBC) constitutes 15-20% of all breast carcinomas, affecting younger women more often and has a worse prognosis than other types of breast cancer, due to the combination of more aggressive clinical behavior and lack of molecular targets for therapy. This study assessed the effects of non-genotoxic concentrations of tributyltin isothiocyanate (TBT-ITC) and triphenyltin isothiocyanate (TPT-ITC) on MDA-MB-231 cells. MATERIALS AND METHODS: MTT assay, comet assay, kinetic imaging and flow cytometry were used for analysis of MDA-MB-231 cells. RESULTS: The results showed that 100 nM concentration of TBT-ITC and TPT-ITC, that did not affect viability or DNA integrity, slowed-down migration by CD44 down-regulation. Moreover, both compounds demonstrated immunomodulatory properties, attenuating PD-L1 expression in MDA-MB-231 cells. CONCLUSION: TPT-ITC was more effective in down-regulating CD44 expression and reducing migration than TBT-ITC, while TBT-ITC was more potent in lowering PD-L1 expression in comparison with TPT-ITC.
Keywords: Triple Negative Breast Neoplasms; Cell Proliferation; Isothiocyanates; pohyb buněk; DNA Damage; nádorové buněčné linie; Cell Line, Tumor; apoptóza; lidé; Humans; isothiokyanatany; nuclear retinoid X receptor; Biomarkers, Tumor; nádorové biomarkery; surface adhesive molecules; proliferace buněk; viabilita buněk; imunofenotypizace; breast cancer; organocínové sloučeniny; protinádorové látky; Apoptosis; Antineoplastic Agents; Cell Movement; poškození DNA; Organotin Compounds; triple-negativní karcinom prsu; DNA damage; migration; immunomodulation; ženské pohlaví; Triorganotin isothiocyanate derivatives; Cell Survival; Female; Immunophenotyping